2019
DOI: 10.3389/fpsyt.2019.00217
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Oxytocin and Increased Homocysteine in First-Episode Schizophrenia Patients

Abstract: Schizophrenia (SZ) is a debilitating and heterogeneous disease. We hypothesized that the oxytocin (OXT) system, inflammation and one-carbon metabolism would have a link with SZ. In this study, serum OXT, OXT receptor (OXTR), interleukin-6 (IL-6), high sensitivity CRP (hsCRP) and homocysteine (Hcy) levels were measured in 52 first-episode schizophrenia (FES) patients and 41 healthy controls (HC) from the Second Xiangya Hospital of Central South University. Meanwhile, the mRNA expressions of OXT and OXTR genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…Our results also showed that FEDN patients had higher prevalence of hyperhomocysteinemia and hyperprolactinemia. Previous studies have also shown significantly increased HC and PRL levels in antipsychotic-naïve schizophrenia and related disorders (11,20). For example, Kirkpatrick et al (13) reported significant differences in PRL levels in patients with schizophrenia compared with controls.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our results also showed that FEDN patients had higher prevalence of hyperhomocysteinemia and hyperprolactinemia. Previous studies have also shown significantly increased HC and PRL levels in antipsychotic-naïve schizophrenia and related disorders (11,20). For example, Kirkpatrick et al (13) reported significant differences in PRL levels in patients with schizophrenia compared with controls.…”
Section: Discussionmentioning
confidence: 96%
“…On phase 3, all participants were invited to provide a blood sample for laboratory tests, including uric acid (UA), homocysteine (HC), total cholesterol (TC), triglyceride (TG) and prolactin (PRL). Previous studies have reported that first-episode schizophrenia populations present with decreased UA levels, increased HC, TC, TG and PRL levels (9)(10)(11)(12)(13). Considering that a substantial body of evidence has accumulated that indicates hypouricemia (40,41), hyperhomocysteinemia (42), hypercholesterolemia (43), hypertriglyceridemia (44) and hyperprolactinemia (45) are associated with cardiovascular risk, it was necessary to investigate hypouricemia, hyperhomocysteinemia, hypercholesterolemia, hypertriglyceridemia and hyperprolactinemia in these patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the study of endogenous oxytocin levels in schizophrenia are mixed. Endogenous peripheral (measured in serum or plasma) oxytocin levels in patients with schizophrenia are lower than those in the healthy population [ 80 , 81 , 82 , 83 , 84 , 85 ], although several studies reported opposite findings [ 86 , 87 ] or no differences [ 88 , 89 ]. Two studies published in the 1980s found that cerebrospinal fluid oxytocin levels are higher in schizophrenia than in the healthy population [ 90 , 91 ], but another study found no difference in levels between individuals with or without schizophrenia [ 92 ].…”
Section: Pathophysiology Of Schizophrenia: Focus On the Role Of Oxmentioning
confidence: 99%
“…Regarding the first of these strands of evidence, there is little doubt that in the cases of bipolar disorder, 71 epilepsy, 45,72 and schizophrenia, [73][74][75] levels of homocysteine and its oxidation product, homocystine, are elevated. This evidence spans many years and too many references for all to be reviewed here.…”
Section: Nnmt -Association With Homocysteine Metabolism and Illnessmentioning
confidence: 99%